2012
DOI: 10.1080/19388160.2012.729402
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Mainland Chinese Tourists' Satisfaction With Hong Kong and the UK Using Tourist Satisfaction Index

Abstract: This study aims to assess mainland Chinese tourists' satisfaction with the UK and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 27 publications
0
18
0
1
Order By: Relevance
“…Later, Song, Li, Veen and Chen (2011) conducted a study to gauge Chinese tourists' satisfaction with three tourism-related service sectors in Hong Kong: hotel, retail, and local tour operators. Using the same tourist satisfaction index approach, Li, Song, Chen and Wu (2012) found that Chinese tourists were more satisfied with Hong Kong than with the United Kingdom as their travel destination. With a growing number of Chinese visiting Hong Kong, some of them expressed dissatisfaction with their travel experience in the destination.…”
Section: Study Methodsmentioning
confidence: 96%
“…Later, Song, Li, Veen and Chen (2011) conducted a study to gauge Chinese tourists' satisfaction with three tourism-related service sectors in Hong Kong: hotel, retail, and local tour operators. Using the same tourist satisfaction index approach, Li, Song, Chen and Wu (2012) found that Chinese tourists were more satisfied with Hong Kong than with the United Kingdom as their travel destination. With a growing number of Chinese visiting Hong Kong, some of them expressed dissatisfaction with their travel experience in the destination.…”
Section: Study Methodsmentioning
confidence: 96%
“…Hospitality is inherent complemented by Zimbabwe's beacon in literacy of the highest standard in the whole of Africa. (www.zimbabwetourism.net) With the center stage the host population has on the identity of destination Zimbabwe, it is important tour operators, and travel agents and immigration are the most commonly acknowledged service-oriented attributes by researchers (Alegre & Garau 2011;Chung & Petrick, 2013;Kozak & Rimmington, 2000;Kresic et al, 2012;Li et al, 2012;Pizam, Neuman, & Reichel, 1978;Song et al, 2012). There are other destination attributes that have received little attention as standalone destination attributes.…”
Section: Destination Attributes and Overall Destination Satisfactionmentioning
confidence: 95%
“…Focus is also on assessing tourist satisfaction with individual destination attributes (Akama & Keiti, 2003;Boukas, 2013;Huang et al, 2010;Ladhari et al, 2008;Lee et al, 2011;Oviedo-García et al, 2014). Though still limited, studies conceptualizing destination attributes as antecedents of overall destination satisfaction have emerged (Alegre & Garau, 2011;Bernini & Cagnone, 2014;Chung & Petrick, 2013;Eusebio & Vieira, 2011;Kozak & Rimmington, 2000;Kresic, Mikulic, & Milicevic, 2012;Li et al, 2012).…”
Section: Destination Attributes and Overall Destination Satisfactionmentioning
confidence: 96%
See 2 more Smart Citations